Fine structure distortion product otoacoustic emission during pregnancy - RAJESH RANJAN; JAYASHREE BHAT; CHRISH JOSEPH (International Journal of Pharma and Bio Sciences, 2016)
Level of both ovarian hormones increases from the normal levels during process of pregnancy, which alter functioning of cochlea affecting hearing sensitivity. Then in order to quantitatively monitor minute changes within the cochlea OAE’s are used. Therefore present study was undertaken with aim to understand the variations in fine structure DPOAE between the three trimesters of pregnancy. Participants included were healthy pregnant women within the age group of 19 – 40 years. Three groups of 30 women each (n=90), grouped on the basis of their trimester of pregnancy (1st, 2nd, or 3rd) participate in this study. Significant effect were observed on fine structure DPOAE (ripple prevalence, ripple density and ripple spacing) when compared across trimesters of pregnant women. Overall fine structure DPOAE across the three trimesters of pregnancy had effect and these effects were more pronounced in the low frequencies hearing.